Madiun Mayor's Social Action In Realizing Smart City Through Social Action Of The Academic Community - Agus Prasetya; Beni Dwi Komara; Dwi Sambada (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2022)
The background of this research is the Research Gap, namely the public service and Iternet Technology matter. The purpose of this research is public service at Madiun City are professional for Madiun community.  Aims research shown the public service by the mayor should run properly and correctly in accordance with its purpose of improving. the quality of public services and the quality of services as a realization of promises in the elections. The misunderstanding of the community that smart City should have been the responsibility of the City government needs to be corrected, all components of the public along with the executive ranks should be held accountable. This research use qualitative research approach is one of the research procedures that produces descriptive data in the form of speech, or writing, and the behavior of the people observed. A qualitative approach is expected to produce an in-depth description of smart City. The data collection techniques of this study were using techniques including in-depth interviews (observation), observation, documentation, with a snowball sampling mode sampling at City government officials, the community. To support the implementation of the research, researchers used the Weber Social Action Theory study. The results showed that Smart City can improve public services, so that citizens are well served. The City Government of Madiun, along with all executive officers, conducts smart cities with good public services from the City government.